Anti-obesity effects of Erythrina abyssinica stem bark extract in flies exposed to a high fat diet - Oscar Hilary Asiimwe; Eddie Wampande; John Rubaihayo; Keneth Iceland Kasozi; Hellen Wambui Kinyi (Heliyon, 2022)
Background: An in vitro assay on Sigmoidin A from Erythrina abyssinica stem bark revealed its potency to inhibit pancreatic lipase. However, studies indicate activity of extract bioactive compounds in combination far exceed the favorable effects of each individual compound due to synergy and additive effects. In this study, we provide information on the effect of E. abyssinica stem bark extract in Drosophila melanogaster. The objective of the study was to determine the safety and effects of E. abyssinica stem bark extract on fly survival, body weight, triglycerides, sterol, total protein, and catalase activity of obese male D. melanogaster. Methods: Obesity was induced by exposing D. melanogaster white mutant w1118 to coconut food for two weeks. Groups 1–3 were fed on coconut food + fenofibrate at 25 mM, 50 mM, and 75 mM. Groups 4–6 were fed on coconut food + E. abyssinica stem bark extract at concentrations of 2.5 g/ml, 5.0 g/ml, and 7.5 g/ml. The positive control was exposed to only coconut food while the negative control was on regular food. Fly survival observations were done for 15 days, while acute and chronic effects were done at 30 min and after 48 h respectively following treatment. Body mass, negative geotaxis, reducing power of the extract, triglycerides (TG/TP), sterol, total protein levels, and catalase activity were measured after 10 days of exposure to the experimental diets. Results: Fly survival changes were observed after 10 days and E. abyssinica stem bark extract had the strongest reducing power at 7.5 g/ml extract concentration. E. abyssinica stem bark extract reduced body mass, triglyceride levels (TG/TP), sterol levels, and modulated catalase activity at 7.5 g/ml extract concentration. Though the standard drug fenofibrate had the highest fat accumulation reduction potential, the extract at 7.5 g/ml was much safer in reducing fat accumulation in obese male D. melanogaster than other concentration used. Conclusion: Antioxidants in E. abyssinica stem bark extract are responsible for the observed anti-obesity activity.